Antifungal Activity of Lactic Acid Bacteria as A Biopreservation in Sourdough Production - Lenni Fitri; Sinta Ayu Mauludin; Sarah Annisa Ananda Putri; Indry Malliny; Nanda Safira; Rahadatul Aisy; Raudhatul Jannah; Zulia Ananda; Dalil Sutekad (Jurnal Bioleuser, 2024)
Bread is a food made from flour and yeast. Bread made using conventional yeast only has limited shelf life because it is susceptible to the growth of fungi such as Aspergillus niger and Rhizopus stolonifer. One way to increase the shelf life of bread is to use Lactic Acid Bacteria (LAB) as a starter for making bread. This research aims to determine the ability of LAB yakult and yoghurt as an antifungal and to test the organoleptic and shelf life of sourdough with LAB formulation. The method used in this research is an experimental methode. The parameters observed were the antifungal activity of yakult and yoghurt with LAB formulation, organoleptic test of sourdough with LAB formulation, and shelf life test of sourdough with LAB formulation. The result showed that yoghurt LAB had antifungal activity, while yakult LAB did not have antifungal activity. Based on organoleptic test, sourdough with the additional of LAB yoghurt has better organoleptic test result compared to white bread without the additional of LAB yoghurt, and sourdough with the addition of LAB yoghurt has a longer shelf life compared to white bread without the additional of LAB yoghurt.